Faktor – Faktor Yang Mempengaruhi Dividend Payout Ratio Pada Perusahaan Pertambangan - Aditya Rizkyta Haryandi; satriyo wibowo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this research is to examine the factors that influence Debt To Equity Ratio, Return On Asset, Size, Earnings Per Share, Cash Position and Total Asset Turnover towards Dividend Payout Ratio. The object used in this research are Mining Companies which listed on the Indonesia Stock Exchange (IDX) from year 2015 to 2020. The research type of this study is quantitative method. This study uses secondary data. The population for this study is 33 sector Mining Companies listed in Indonesia Stock Exchange from year 2015 to 2020. The data were analyzed using multiple regressions analysis method to determine the model of research. The result of this research is that Debt To Equity and Return On Asset negatively affect the Dividend Payout Ratio. Then Size, Earnings Per Share, and Total Asset Turnover have a positive effect on the Dividend Payout Ratio. Meanwhile, Cash position does not affect the Dividend Payout Ratio.